Recent progress in the development of SiC composites for nuclear fusion applications - Koyanagi, T.; Katoh, Y.; Nozawa, T.; Snead, L.L.; Kondo, S.; Henager, C.H.; Ferraris, M.; Hinoki, T.; Huang, Q. (Journal of nuclear materials, 2018)
Silicon carbide (SiC) fiber reinforced SiC matrix composites continue to undergo development for fusion applications worldwide because of inherent advantages of the material including low activation, high temperature capability, relatively low neutron absorption, and radiation resistance. This paper presents an international overview of recent achievements in SiC-based composites for fusion applications. Key subjects include applications in fusion reactors, high-dose radiation effects, transmutation effects, material lifetime assessment, and development of joining technology (processing, test method development, irradiation resistance, and modeling capability). This paper also discusses synergy among research for fusion materials and non-fusion materials (for fission and aerospace applications). Finally, future research directions and opportunities are proposed.